Таңдау компоненті ретінде интеллектуалды жүйелер пəнін оқытуды жетілдіру - Қосыбаева, У.А. (ҚарМУ баспасы, 2012)
Вступление человечества в ХХI век требует стратегического развития общества на основе знаний и высокоэффективных технологий. В статье рассматриваются проблемы развития интеллектуальных систем, взаимоотношения между человеческим разумом и компьютером. Цель создания искусствен- ного интеллекта — снизить интеллектуальную нагрузку, лежащую на современном человеке. Преподавание интеллектуальных систем в вузе дает возможность применить интеллектуальные системы при решении проблем, связанных с потоками информационного прогресса в профессиональной сфере. The introduction of humanity into XXI century demands transition to new strategy of development of a society on the basis of knowledge and highly effective technologies. The purpose of creation of an artificial intellect- to lower the intellectual loading laying on the modern person. Training of the student taking into account his individual opportunities is carried out with the help of special tests. In the articles there is considered the problem of creation of an artificial intellect, mutual relation between human reason and a computer, and also the analyze of numerous tests. The Teaching of Intelligent Systems at the university gives the opportunity to apply intelligent systems for solving problems related to the information flow progress in the professional sphere.
Keywords: интеллектуалды жүйелер; оқытуды жетілдіру; таңдау компоненті